APLIKASI TEORI VIRGINIA HENDERSON PADA PASIEN NEGLECTED FRACTURE OF LEFT SHAFT FEMUR - Sahrudi; Masfuri; Waluyo, Agung (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
Nursing care provided by nurses greatly influences the quality of health services that patients willreceive. One of the efforts taken to improve the quality of nursing care is by applying VirginiaHenderson's theory. Objective: Application of Virginia Henderson's theory to patients with theNeglected Fracture of Left Shaft Femur. The methodology used case studies. Results: Theapplication of Virginia Henderson's theory was effectively applied to patients with the NeglectedFracture of Left Shaft Femur. Conclusion: Virginia Henderson's theory can be used in nursingcare for patients with Neglected Fracture Left Shaft Femur to increase independence due tophysical and psychological changes.